Experimental and Simulation of CNC Milling Process Towards Product Quality of Mild Steel - Amir Malli, Nurul Liyana (Progress in Engineering Application and Technology, 2023)
The surface finish is used to gauge the machining's quality. It is essential to adjust the machining parameters properly and optimally during the machining process to improve the surface quality. Since CNC machines are extremely sophisticated machinery based on the previous study there are a few of the problems that occur in CNC machining are frequently caused by programming. The aim of this experiment is, to simulate the changing of the feed rate and spindle that can affect the cycle time. Besides, to analyze the effect of simulation by using Mastercam software and machining the surface by using CNC milling and checking the quality of the surface using a surface roughness machine. The importance of this research is that it can speed up machining by using simulation. Additionally, it can increase productivity with quality when run on a machine. From there, it can be shown that the simulation’s expected time is accurate because it is virtually identical to actual time machining. Other than that, feed rate and spindle speed are the variables that were evaluated, which is three different feed rate 200mm/rev, 300mm/rev, and 400mm/rev, and three different spindle speed which is 1300 rpm, 1400 rpm, and 1500 rpm to obtain the best machining time and surface quality on workpieces. As a result, the feed rate has a greater impact on machining time during the operation.  Based on the outcomes of the experiment changing the parameter of spindle speed can affect the surface roughness result, the spindle speed is the most significant element impacting the surface roughness.